Caracterização estrutural, dinâmica e reológica de suspensões coloidais via simulação molecular - Oliveira, Fellipe Carvalho de (2016)
In the oil industry, the deposition of heavier fractions, paraffins and asphaltenes, cause problems related to flow assurance. In the early stages of solid precipitation process gels and/or colloidal suspensions are formed. It is necessary studiyng the particle aggregation dynamics to understanding the dynamic mechanisms of paraffins and asphaltenes precipitation. The goal of this work was the implementation of algorithms that calculate structural (Radial Distribution function (RDF) and Structure Factor), dynamical (diffusion coefficient and viscosity) and rheological (G0 and G00 ) properties under different conditions. The validation and tests of these algorithms are made by comparing with literature results of a LennardJones fluid under different conditions. The methods are used to calculate structural and dynamic properties of systems in aggregation process (gelation) obtained via Brownian Dynamics. Brownian dynamics was used, because it allows to insert the solvent influence in the simulation as well as it permits larger timescales. Structural analysis showed that the gels structure continuously on the simulation timescale. The diffusion coefficient decreased along with the time (gelification) and tends towards a constant value, this means that the system does indeed form large aggregates which is confirmed by the Structure Factor. Rheological analysis was performed by oscillatory test which shows that the suspensions exhibit viscoelastic behavior. Elastic behavior prevails at high oscillation frequencies while viscous behavior prevails at low frequencies. Rheological analysis also demonstrated that the gel ages over the simulated time by the increase of the modules G0 and G00 .